2020
DOI: 10.1177/0569434520974258
|View full text |Cite
|
Sign up to set email alerts
|

Who Publishes in Economic Education? A Bibliographic Analysis of the First 50 Years of the Journal of Economic Education

Abstract: We examined the characteristics of the authors who published academic articles in the Journal of Economic Education ( JEE) during its first 50 years and identify those economists who were most productive in developing economic education as a specialized field. Employing bibliometric data, we review trends in the salient characteristics of authorship with special attention paid to gender, geography, institutional affiliation, and other factors. We also explore the JEE’s impact on the development of teaching-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Economists have a long tradition of studying the craft of teaching through the lens of their discipline (Grimes and Mixon 2021). For more than half a century, economic educators have used their classrooms as laboratories to model the production of economics human capital.…”
Section: Background and Literaturementioning
confidence: 99%
“…Economists have a long tradition of studying the craft of teaching through the lens of their discipline (Grimes and Mixon 2021). For more than half a century, economic educators have used their classrooms as laboratories to model the production of economics human capital.…”
Section: Background and Literaturementioning
confidence: 99%
“…In the analysis of the role of women in economics, there has been minimal investigation into women’s participation in pedagogy research. Grimes and Mixon (2021) have shown that women are a growing percentage of authors in the economic education space. From the 1970s until the end of the 2010s, women have increased authorship in the Journal of Economic Education ( JEE ) from around 10% to nearly 25%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since Harter et al (1999) showed that instructor gender matters when it comes to delivering curriculum at the undergraduate level, it is possible that male and female experiences with scholarship also differ. In fact, a recent paper by Grimes and Mixon (2021) found that less than 25% of all authors who contributed to the Journal of Economic Education from 2010 to 2019 were women. Though these initial findings suggest that female authorship rates in economic education generally replicate women's representation in economics, they still leave us to question what the specific experiences of female researchers are, and what can be done to make the subfield a more attractive and accessible avenue for their scholarship.…”
Section: Introductionmentioning
confidence: 99%